Investigation in Nano III-V ternary InxGa1-x P semiconductor materials by chemical vapor deposition - Alla, Srivani; vedam, Ram murthy; Veeraraghavaiah, G. (International Journal of Physical Research, 2014)
Phosphides of group III have generated important applications in optoelectronic devices. Principally InxGa1-xP is a novel alloy for the development of solid-state lighting and photovoltaic systems, since it is possible to control its band gap from 2.26 eV to 1.27 eV by simply varying the indium concentration. However during the growth of InxGa1-xP inherent defects are obtained in the material, degrading its optical properties. In this work, the effect of the indium concentration is studied. The results of the optical and structural characterization of a series of InxGa1-xP films (0 < x < 0.3) deposited by chemical vapor deposition (CVD) are reported. Keywords: Inxga1-Xp, Semiconductor; Luminescence and Optoelectronics.